Emerging Roles of Mucosal-Associated Invariant T Cells in Rheumatology - Li, Yanmei; Du, Jun; Wei, Wei (Frontiers in Immunology, 2022)
Mucosal-associated invariant T (MAIT) cells are an unconventional T cell subset expressing a semi-invariant TCR and recognize microbial riboflavin metabolites presented by major histocompatibility complex class 1-related molecule (MR1). MAIT cells serve as innate-like T cells bridging innate and adaptive immunity, which have attracted increasing attention in recent years. The involvement of MAIT cells has been described in various infections, autoimmune diseases and malignancies. In this review, we first briefly introduce the biology of MAIT cells, and then summarize their roles in rheumatic diseases including systemic lupus erythematosus, rheumatoid arthritis, primary Sjögren’s syndrome, psoriatic arthritis, systemic sclerosis, vasculitis and dermatomyositis. An increased knowledge of MAIT cells will inform the development of novel biomarkers and therapeutic approaches in rheumatology.